Non-Associative Geometry of Quantum Tori - D'Andrea, F.; Franco, D. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We describe how to obtain the imprimitivity bimodules of the noncommutative torus from a ''principal bundle'' construction, where the total space is a quasi-associative deformation of a 3-dimensional Heisenberg manifold.